The treatment of patients with low tumour burden and/or slow growing disease. - Maughan, T (2011)
In the evaluation of the wide range of novel therapeutics which have been developed, investigators do not have to be tied to the current paradigm of demonstrating additive efficacy to first line combination therapy. The addition of new agents to FOLFOX regimens has proved a high hurdle at which many promising agents have fallen. In those patients with slow growing disease or low tumour burden both the use of novel agents in a window of opportunity trial before conventional chemotherapy or in combination with single-agent first line chemotherapy may be useful strategies to test efficacy in relatively untreated patients. Further the evaluation of novel therapies in the chemotherapy-free interval allows the use of single-agent treatments early in the disease course with time to progression as a meaningful endpoint for clinical benefit and to give clear data of efficacy. The most important point from this discussion of the management of patients with slow growing metastatic colorectal cancer is the requirement of the oncologist to have a patient-centred perspective, varying management from standard paradigms to meet patients' needs. We need to consider that this patient may be alive for 3-6 years and we must maximise quality of life as well as survival. That means the patient should be enabled to live as normal a life as possible for as much time as possible. Therefore the selective use of chemotherapy, the use of sequential therapy and of chemotherapy-free intervals is of great importance and can achieve major benefits for our patients. © 2011 Elsevier Ltd.